The Influence of System Quality, Information Quality, and Service Quality on User Satisfaction with the Follow-up Monitoring Information System (SIPTL) in East Java Province - Ahiroh, Ahiroh; Dadang Suwanda; Marja Sinurat (Sean Institute, 2025)
In accordance with technological developments, the BPK has developed a Follow-up Monitoring Information System (SIPTL) application that is utilized by audited entities (auditees) to submit supporting evidence documents for follow-up on BPK audit recommendations more quickly, well documented and produce more up-to-date, accurate and informative TLRHP data. This study aims to determine and analyze the effect of system quality, information quality and service quality on SIPTL user satisfaction in East Java Province. The method used is a quantitative method, data collection using purposive sampling techniques through questionnaires. Data analysis using SEM-PLS with the help of Smart-PLS software. With the test resultsβsystem quality=0.382,βinformation quality=0.229 andβservice quality = 0.318. The value of R = 0.791, R2 = 0.626, f2 information quality = 0.065, f2 service quality = 0.174 and f2 system quality = 0.201, t-test system quality = 4.371, t-test information quality = 2.723 and t-test service quality = 4.245 and Q2 Predictive Relevance = 0.592. Based on the test results, H1 is accepted that there is a significant influence of system quality on user satisfaction of 38.2%, there is a significant influence of information quality on user satisfaction of 22.9% and there is a significant influence of service quality on user satisfaction of 31.8%. Efforts that can be made to increase the influence of system quality, information quality and service quality on SIPTL user satisfaction in East Java Province are improving compatibility on mobile devices, optimizing system performance, increasing the responsibility of the SIPTL support team, periodic evaluation and monitoring and developing interactive features for users.